Semantic models of sound-driven design: Designing with listening in mind. (November 2022) - Monache, Stefano Delle; Misdariis, Nicolas; Özcan, Elif
Abstract : Sound-driven design is a design practice informed by technology and listening in the multisensory dimension of interaction. An automated content analysis of 20 semi-structured interviews with sound designers, design researchers, engineers and expert users stressed the inherently embodied and situated conceptualisation of sound, and how it relates to their professional activity. The four categories of professionals bring in different designerly orientations towards sound. Listening, as a way of knowing by using sound in interaction, proves to be the red thread between the participants' semantic models. Overall, the findings contribute to characterise the concept of sound in current design practices, and position the role of nonverbal, yet auditory representations in the design process. Highlights: Sound-driven design focuses on technology and listening in action. Professionals involved in sound and design brings in different listening cultures. Designing [the, with, against] sound [for] are active forces in the design process. Listening adds to the understanding of the multisensory nature of designing.